Um clássico in versões: representações de infância em textos verbais e imagens de Chapeuzinho Vermelho - Flavia Graciela de Alcantara (2009)
This research developed based on a transdisciplinary approach between Literature, Education and History, analyzing intertextual and interdiscoursive aspects of versions of the classic childrens story, Little Red Riding Hood, in relation to childhood conceptions perceived in different historical periods. This study was guided by the following questioning: What representations of childhood can be perceived through the reading of versions written during distinct historical periods? What types of alterations did this childrens tale suffer based on differentiated forms of conceiving childhood? What discoursive marks determine the differences between the versions of this classic tale? Do the intertextual components reveal the existence of a reader profile awaited or desired? So as to reflect on such questioning, the following versions of Little Red Riding Hood were selected for this paper: Chapeuzinho Vermelho, by Figueiredo Pimentel; excerpts from Reinacoes de Narizinho and O Picapau Amarelo by Monteiro Lobato, in which Capinha Vermelha appears; Chapeuzinho Amarelo by chico Buarque and A Verdadeira Historia de Chapeuzinho Vermelho by Agnese Baruzzi and Sandro Natalini. The works were chosen based on the base text, Le petit chaperon rouge, part of the Contes de Perrault collection, by Charles Perrault in 1697, reedited in 1880, in Paris, and were analyzed in significant periods of the history of Brazilian childrens literature. Discourse Analysis was utilized as the methodological procedure to comprehend different childhood representations and the place attributed to them by way of the literary discourse. While analyzing works in versions of this classic of childrens literature, one notices that a myriad of inversions in the linguistic organization, lexical and discoursive semantics, of the narratives permeated its production process, distribution and consumption, influenced by the reader or child listener who would make use of them, who represented a specific notion of childhood, determined by temporal, cultural and social marks.